2018
DOI: 10.3390/met8090654
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum and Niobium Selective Extraction by Alkyl-Acetophenone

Abstract: Abstract:A study has been carried out on Ta and Nb recovery by a liquid-liquid extraction process using 4-methylacetophenone (4-MAcPh) as the organic phase. The 4-MAcPh was compared to methyl isobutyl ketone (MIBK) with respect to extraction efficiencies (D values) at different concentrations of H 2 SO 4 in the aqueous phase. The results showed a similar extraction of Nb for both solvents. However, for Ta, extraction efficiency is increased by a factor of 1.3 for 4-MAcPh. In addition, the MIBK solubilized comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Further purification, by selective extraction of tantalum from an acid leaching solution, has been proposed using ILs instead of an organic solvent in a liquid-liquid extraction process. To emulate the role of the organic solvents used for Ta extraction, such as methyl iso-butyl ketone (MIBK) or tri-butyl phosphate (TBP), ILs were rendered task-specific by functionalizing them with ketone or phosphonate groups, successfully making them selective to tantalum for its extraction from a sulfuric acid leachate [149][150][151].…”
Section: Recycling At the Electronic Components Level: Processes And Opportunitiesmentioning
confidence: 99%
“…Further purification, by selective extraction of tantalum from an acid leaching solution, has been proposed using ILs instead of an organic solvent in a liquid-liquid extraction process. To emulate the role of the organic solvents used for Ta extraction, such as methyl iso-butyl ketone (MIBK) or tri-butyl phosphate (TBP), ILs were rendered task-specific by functionalizing them with ketone or phosphonate groups, successfully making them selective to tantalum for its extraction from a sulfuric acid leachate [149][150][151].…”
Section: Recycling At the Electronic Components Level: Processes And Opportunitiesmentioning
confidence: 99%
“…The formed white wet cake was washed with deionized water, transferred to a glass beaker, and dried in vacuum oven for 48 h at 135°C (WOCT-135) to ensure that all the organic solvents were removed. The dried cakes were placed in a porcelain crucible for calcination at 1050°C for 3 h in a muffle furnace (WOCT-1050) 61,62 . The annealed grey metal oxide was milled and further used after washing in ethanol and distiller water (WOCT) in this study (photo all the extraction process shown on the Supplementary Fig.…”
Section: Mineral Extractionmentioning
confidence: 99%
“…The selectivity of the ligands for Ag + relative to Cu 2+ and Pb 2+ was determined as follows 32 : The Ag + complexes of ligand 1 were synthesized following the procedure reported by Daubinet 33 . Briefly, the ligand 1 (1 eq.)…”
Section: Ag + Uptake Studiesmentioning
confidence: 99%